ChemInform Abstract: Catalytic Transformations of Organic Compounds and Biomass Derivatives with Functionalized Metal‐Organic Frameworks. Issue 23 (May 2016) - Liu, Xiaofang; Zhang, Heng; Chang, Fei; Huang, Shan; Yang, Kaili; Yang, Song
Abstract: Review: 116 refs.